Free-standing and consecutive ZnSe@carbon nanofibers architectures as ultra-long lifespan anode for flexible lithium-ion batteries. (April 2022) - Zhang, Teng; Qiu, Daping; Hou, Yanglong
Abstract: Free-standing electrodes have attracted extensively attention for their absence of non-electrochemical activity binders, conductive additives, and current collectors. Here, the fordable and flexible ZnSe@carbon nanofibers (ZnSe@CNFs) composites have been synthesized via electrospinning method and subsequent one-step carbonization/selenization process. Benefited by the structural advantage of ZnSe nanoparticles encapsulated inside carbon nanofibers conductive network, this delicate electrode exhibits superior electrochemical performance, including outstanding rate capability and ultra-long cycling life (426.1 mAh g −1 over 3000 cycles at 5 A g −1 with only 0.01% decay per cycle). More importantly, the free-standing electrode could be further applied in pouch cell, which delivers prominent capacity of 448.9 mAh g −1 during 700 cycles at 0.5 A g −1 . What's more, this pouch cell successfully lightens the luminescence of the light-emitting diodes (LEDs). Even if we repeatedly fold 30 times at different angle (90°, 180°, and 0°), the pouch cell is still in good agreement with the pristine stage. This design is beneficial to propel the development of free-standing electrode in the aspect of flexible/wearable electronic devices. Graphical Abstract: ga1 Highlights: Flexible and free-standing ZnSe@carbon nanofibers electrodes are designed by one-step electrospinning methods. Outstanding rate capability and ultra-long cycling life over 3000 cycles at 5 A g −1 are achieved. Ex-situ XRD reveals the internal lithium storage mechanism of ZnSe. The large-area pouch cell is successfully assembled and operated at different bending angles.